Application of Internet marketing tools for management decision-making by logistics enterprises - O.A.; T.O.; O.P.; H.Yu. (Економіка, управління та адміністрування)
The article discusses implementing Internet marketing tools by logistics enterprises for the management of decision-making processes. The use of Internet marketing tools, in particular, targeted advertising on Facebook, by logistics businesses and enterprises was studied. The essence of the concepts of «targeted advertising», «conversion» and «Facebook Pixel» was defined. The algorithm for setting up targeted advertising on Facebook for logistics enterprises was developed and the forecast of the effectiveness of advertising campaigns in 2022 was made. It is proposed to use the Pixel Facebook code for the company’s website in order to analyze the effectiveness of advertising campaigns and use the data obtained with the subsequent stages of remarketing. The steps of creating advertising campaigns for logistics enterprises using the Ads Manager cabinet from Facebook are obtained. The use of advertising campaigns with the goals of «reach», «traffic» and «conversion» for broadcasting paid advertisements on Facebook is justified. Thus, the use of the type of advertising campaign with the goal of «reach» will contribute to the growth of the level of brand recognition and maximum coverage of the target audience, and the creation of advertising campaigns with the goal of «traffic» will allow to increase the flow of potential customers. It was determined that additional traffic to the site from targeted advertising would allow the formation of a target audience group using the Facebook Pixel. The direct influence of the size of the advertising budget on the predicted indicators of targeted advertising has been proven. The share of the number of businesses and enterprises having a website was analyzed. It was determined that the share of the number of enterprises having a website in 2018 was 35,6 %, in 2019 – 35,2 %, and in 2021 – 35,3 %. This indicates a low level of digitalization of business entities and limited opportunities in finding new sales channels for products (services). It is proposed to implement management solutions through the implementation of Internet tools marketing for logistics enterprises. The paper considers the need to develop a website to increase the flow of customers and/or expand product sales channels (providing services).